2000
DOI: 10.1021/bi991091j
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Loop Containing Residue 115 in the Induced-Fit Mechanism of the Bacterial Cell Wall Biosynthetic Enzyme MurA

Abstract: The induced-fit mechanism in Enterobacter cloacae MurA has been investigated by kinetic studies and X-ray crystallography. The antibiotic fosfomycin, an irreversible inhibitor of MurA, induced a structural change in UDP-N-acetylglucosamine (UDPGlcNAc)-liganded enzyme with a time dependence similar to that observed for the inactivation progress. The mechanism of action of fosfomycin on MurA appeared to be of the bimolecular type, the overall rate constants of inactivation and structural change being = 104 M(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 15 publications
(26 reference statements)
3
70
0
Order By: Relevance
“…The inactivation rate of MurA with fosfomycin is also dependent upon UDP-GlcNAc (8). Surprisingly, the second-order inactivation rate of MurA by bromoacetate, under saturating UDPGlcNAc at pH 8.0, is only 9-fold slower than by fosfomycin under saturating UDP-GlcNAc at pH 6.9 (104 M −1 s −1 ) (26).…”
Section: Resultsmentioning
confidence: 95%
“…The inactivation rate of MurA with fosfomycin is also dependent upon UDP-GlcNAc (8). Surprisingly, the second-order inactivation rate of MurA by bromoacetate, under saturating UDPGlcNAc at pH 8.0, is only 9-fold slower than by fosfomycin under saturating UDP-GlcNAc at pH 6.9 (104 M −1 s −1 ) (26).…”
Section: Resultsmentioning
confidence: 95%
“…They concluded that PEP inside the catalytic center was protonated and the enzyme stabilized an oxacarbenium ion upon binding with UDP-GicNAc. The substrate-induced conformational change was later demonstrated in both crystal structure (7,25,26) and fluorescence experiments (21).…”
Section: Evidence Of Oxacarbenium Ion In Addition Stepsmentioning
confidence: 99%
“…PEP also interacts with it to form a covalently linked phospholactoyl-enzyme adduct. Cys115 is located in a loop which undergoes a large conformational change as the enzyme binds to the substrates (26). Site-directed mutagenesis experiments suggest it acts as a general acid in protonating the C3 position in the addition step, and a general base for decomposition of THI in both forward and backward directions (11).…”
Section: Important Catalytic Residuesmentioning
confidence: 99%
“…However, the discovery that Cys-115 could be replaced by an aspartate without loss of activity (a mutation found in some bacteria including Mycobacteria) led to the conclusion that Cys-115 functions as a general acid-base catalyst and not as a nucleophile in the reaction with PEP (10). Cys-115 is a member of a 10-residue loop in the N-terminal globular domain that undergoes drastic conformational changes upon binding of UNAG by approaching the interdomain cleft and positioning the Cys-115 side chain into the PEP binding site (11)(12)(13)(14)(15). Cys-115 has received considerable attention as the target of covalent modification by fosfomycin (12) and other electrophilic natural products such as terreic acid (16) and cnicin (17).…”
mentioning
confidence: 99%